Photosynthetic Properties of ac-31, a Mutant Strain of Chlamydomonas reinhardi Devoid of Chloroplast Membrane Stacking - Goodenough, Ursula W. (1969)
A pale-green mutant strain of Chlamydomonas reinhardi, ac-31, is characterized by the absence of any stacking of its chloroplast membranes. The capacity for photosynthetic electron transport, phosphorylation, and CO(2) fixation in ac-31 is substantial, and it is concluded that these photosynthetic activities occur within the single membrane. The photosynthetic capacities of wild type and ac-31 as a function of increasing light intensity are compared. Saturation is attained at higher light intensities in ac-31, and the kinetics of the 2 sets of curves are distinctly different. The possibility that energy transfer is enhanced by membrane stacking is suggested by these results. The repeatedly-observed correlation between reduced stacking and disfunctional Photosystem II activities is discussed in view of the observation that ac-31 has no stacking but retains a functional Photosystem II.